2019
DOI: 10.1038/s41598-019-47439-3
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of the MLH1 V384D germline mutation in patients with HER2-positive luminal B breast cancer

Abstract: HER2-positive luminal B breast cancer (BC), a subset of the luminal B subtype, is ER-positive and HER2-positive BC which is approximately 10% of all BC. However, HER2-positive luminal B BC has received less attention and is less represented in previous molecular analyses than other subtypes. Hence, it is important to elucidate the molecular biology of HER2-positive luminal B BC to stratify patients in a way that allows them to receive their respective optimal treatment. We performed molecular profiling using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…In addition, another study that sequenced MMR genes in 12,019 cancers comprising 32 cancer types reported less than 2% frequency of MMR deficiency in breast cancer [36]. Furthermore, a recent study in 94 HER2-positive luminal B breast cancer patients showed that, although 13.5% of cases had a germline mutation (V384D) in the MLH1 gene, only 3 cases (3.2%) were MLH1-deficient by IHC [37]. In contrast, a recently published cohort from Italy reported a ten-times higher frequency (17%, 75 out of 444 cases) of homogenous MMR loss by immunohistochemistry [30]; although when further investigated by microsatellite instability assay, all but seven of these were negative (meaning only 1.6% of cases overall were MSI positive).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, another study that sequenced MMR genes in 12,019 cancers comprising 32 cancer types reported less than 2% frequency of MMR deficiency in breast cancer [36]. Furthermore, a recent study in 94 HER2-positive luminal B breast cancer patients showed that, although 13.5% of cases had a germline mutation (V384D) in the MLH1 gene, only 3 cases (3.2%) were MLH1-deficient by IHC [37]. In contrast, a recently published cohort from Italy reported a ten-times higher frequency (17%, 75 out of 444 cases) of homogenous MMR loss by immunohistochemistry [30]; although when further investigated by microsatellite instability assay, all but seven of these were negative (meaning only 1.6% of cases overall were MSI positive).…”
Section: Discussionmentioning
confidence: 99%
“…Overall survival (c) and breast cancer diseasespecific survival (d) in ER-positive, tamoxifen-treated patients of higher specificity achieved through curated genomic methods versus a higher sensitivity using protein expression detected through IHC methods [19]. We opted for IHC because MMR deficiency in breast cancer patients is very rarely hereditary [37,43]. Additionally, IHC is wellestablished in colorectal cancer and endometrial cancer, inexpensive and readily available [40,44].…”
Section: Discussionmentioning
confidence: 99%
“…In line with the heritability of some cancers, several germline variants predict a patient's risk for developing cancer and are useful for individualizing cancer screening guidelines [4][5][6][7][8][9][10][11][12][13]. Germline variation can affect drug sensitivity, predict drug toxicity, and could help select therapy to minimize side-effects [14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Genomic scars in the MMR system are relatively rare in breast cancer, being reported in~2% of cases [49]. However, this subject is controversial in literature given the lack of companion diagnostics and/or tumor-specific guidelines for MMR analysis [47,[49][50][51][52][53][54]. Unlike in endometrial and colorectal cancers, MSI is restricted to a minority of breast cancers showing MMR protein loss [54].…”
Section: Nuclear Pten and Modulation Of The Dna Damage Responsementioning
confidence: 99%